The importance of nursing care for patients with Alzheimer's (Research, Society and Development, 2022)
Objectives: To analyze the importance of nursing care for Alzheimer's patients. Methodology: The research is a study carried out through an integrative literature review. The databases of the Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (Lilacs) and Medical Literature Analysis and Retrievel System Online (Medline) and the health sciences descriptors (DECS) were used. Nursing care; Elderly and Alzheimer's Disease and full text in Portuguese. Results And Discussion: The nurse is the professional who works directly in the educational activities provided to the community, playing a role of fundamental importance in society in order to provide and promote the empowerment of the elderly. care for users, seeking alternative ways that may lead to attitudes that provide them with full health in the broadest sense. Conclusion: It appears that nursing care goes beyond the elderly with the pathology, attention is needed for the person who takes care of them, because with all the responsibility on the individual, there will certainly be an overload of responsibilities, which will cause damage to their health. . It is important to highlight that the caregiver is an essential being during the care process.